A educação no MST: experiências educativas no Centro de Formação do Assentamento Antônio Companheiro Tavares-PR, 1998-2012 - Pedron, Simone Tatiana (2012)
This study deals with the educational experiences of rural workers at the Educational Center for Landless Rural Workers (MST) of the Antônio Companheiro Tavares Settlement, located in the Municipality of São Miguel do Iguaçu, in the west of the State of Paraná, between 1998 and 2012. The focus of this research was to observe how workers (students, settlers and teachers) interpret and attribute meanings to the MST's educational proposal and how its dimensions permeate the social relations within the settlements. At the same time, Rural Education was identified as a process of political education. The objective of this education―focused on a praxis experienced―is the continuity of the MST's struggle for land and the agrarian reform, since school and the multiple dimensions of the daily life comprise spaces for education of these individuals that develop concepts of rights and struggle collectively for them. Oral interviews―basic sources of the research―provided significant signs for the understanding of workers' educational practices, highlighting a process of re-signification of the experiences of these subjects, who constitute themselves through struggle and the multiplication of a Landless' educational project